Development of a Particulate Matter and Carbon Monoxide Detector - Aribisala, Adetoye Ayokunle; Dada, Jacob Babatunde; Abdulrauf, Ridwanullahi Opeyemi (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Air pollution is inarguably a common tragedy in the today’s world: a resultant effect of industrialization and civilization. This work considered two of the most common domestic air pollutants – particulate matter (PM) and carbon monoxide (CO). This developed device is able to detect the presence of these two pollutants in the atmosphere, and trigger an alarm when the levels of these pollutants is above the safe level with respect to the World Health Organization (WHO) standards. NOVA SDS011 and MQ135 were used as the particulate matter and carbon monoxide sensors respectively, 20 x 4 Liquid Crystal Display (LCD) was used as the display unit, and a buzzer as the alarm device which is triggered when the pollutant level is high. The device utilizes Arduino Uno R3 as its microcontroller for controlling the operation of the device. The key contribution to knowledge of this work is the design of a low-cost, portable and modern pollutant detector that can be traditionally deployed in either closed or open environments. On testing the device under different conditions for 500 seconds per condition, the indoor PM2.5, P.M10 and CO levels ranged between 16-19 µg/m3, 43-80 µg/m3 and 0.6-1.3 parts per million (PPM) respectively. The outdoor PM2.5, PM10 and CO levels were between 17-23 µg/m3, 19-62 µg/m3 and 0.3-0.6 PPM respectively. These levels are considered reasonable enough compared to World Health Organization safe limits of below 25 µg/m3, below 54 µg/m3 and 9 PPM for the PM2.5, PM10 and CO respectively. The device was further exposed to the combustion of fuels and to a dusty environment to read very unsafe limits. This work helped to develop a cost-efficient pollution detector; even as optimal operating efficiency was retained.